The Invention of Literary History in Cicero's Brutus. - van den Berg, Christopher S. (Classical Philology, 2019)
A literary criticism of the Roman oratory "Brutus" written by the Roman statesman Cicero. Topics discussed include methodological advance over the works of previous Hellenistic and Roman scholars; emphasis on prosopography, history of early poetry, and textual economy of Cicero's work and afterlife; and examination of literary history, including a nuanced account of its intellectual potential and methodological problems.